Transparência da informação pública: uma avaliação de sítios eletrônicos de universidades federais brasileiras - Melo, Douglas Arrais (2019)
The regulation of access to information in Brazil, through the Access to Information Act (AIA), represents the reaffirmation of the practice of transparency as a key component of the credibility and effectiveness of State actions before civil society. With the high production of public information and the demand for agility and fluency in its processing, the Internet has been the main mainstay of this access. In this context, if information on public-electronic sites is unavailable, incomplete and/or incomprehensible, they impact on the factual compliance of AIA and the promotion of transparency in a whole. This dissertation, therefore, had as main objective to classify the quality of the information available in the electronic websites of Brazilian federal universities in accordance with the principles of transparency proposed by AIA. It was proposed the development of a transparency index with a focus on information as a “product”, with attributes determined by a mainly intuitive-theoretical approach, based on publications of the federal government and studies by Amorim and Almada (2016) and Silva and Carreiro (2013). The index was applied to the websites of the twenty best federal universities according to the General Course Index (GCI) of 2017. The main results identified: the more and less transparent information, the more and less transparent sites and the benchmarks. The quality of the information of the sites was verified with precision, which was not very transparent, insufficient for the citizen’s understanding. This appeared to indicate little involvement of the public officials responsible for these sites to comply with the law. Together with a reliable instrument of transparency, awareness, union and social action in favor of the culture of transparency are fundamental to the evolution of access to information in Brazil and, intrinsically, of social participation and control.